2020
DOI: 10.1098/rspb.2020.0675
|View full text |Cite
|
Sign up to set email alerts
|

Biotic stability mechanisms in Inner Mongolian grassland

Abstract: Biotic mechanisms associated with species diversity are expected to stabilize communities in theoretical and experimental studies but may be difficult to detect in natural communities exposed to large environmental variation. We investigated biotic stability mechanisms in a multi-site study across Inner Mongolian grassland characterized by large spatial variations in species richness and composition and temporal fluctuations in precipitation. We used a new additive-partitioning method to separate species synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(53 citation statements)
references
References 62 publications
3
50
0
Order By: Relevance
“…S4, S5), which suggests that their relationship is context dependent. We found that the effect size of β diversity on spatial asynchrony increased with the amount and variability of precipitation (Table 1), coinciding with recent findings that the stabilizing effect of biodiversity in naturally assembled grasslands increases along a precipitation gradient (Hallett et al 2014), as long as aridity is not too extreme where it can reverse the relationship (Wang et al 2020). Future experiments are required to test the context dependence of β diversity in regulating ecosystem stability.…”
Section: Discussionsupporting
confidence: 90%
“…S4, S5), which suggests that their relationship is context dependent. We found that the effect size of β diversity on spatial asynchrony increased with the amount and variability of precipitation (Table 1), coinciding with recent findings that the stabilizing effect of biodiversity in naturally assembled grasslands increases along a precipitation gradient (Hallett et al 2014), as long as aridity is not too extreme where it can reverse the relationship (Wang et al 2020). Future experiments are required to test the context dependence of β diversity in regulating ecosystem stability.…”
Section: Discussionsupporting
confidence: 90%
“…Current global environmental change is causing increasing interest in the role of abiotic factors in the long‐term sustainability of ecosystems (De Laender et al., 2016; Mazzochini et al., 2019; Wu et al., 2021). Recent studies have indicated that abiotic drivers (e.g., environmental conditions, such as climate, soil and topography) might obscure the true magnitude and direction of biodiversity on the functioning and stability of ecosystems (Coelho de Souza et al., 2019; Gross et al., 2017; Wang et al., 2020). Environmental heterogeneity is also an important abiotic factor affecting biodiversity and stability (Oliver et al., 2010; Stein et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the effect of species diversity on life‐history ecosystem linkages may be contingent on the evenness of plant species abundances in the community. Plant species richness is often driven by low abundance species (Grime, 1998) while a few dominant species contribute to most of the cover and biomass (Avolio et al., 2019; Wang et al., 2020; Whittaker, 1965). For instance, in a central US grassland, large reductions of species richness through removal of low abundance species had little effect on ecosystem production, which was driven by a few dominant species (Smith & Knapp, 2003).…”
Section: Discussionmentioning
confidence: 99%